THE INFLUENCE OF SERVICE QUALITY AND COMPANY IMAGE ON CONSUMER SATISFACTION AT CARRO INDONESIA.ID HARAPAN INDAH BEKASI BRANCH - Muhamad, Muhamad Chaerul Ikhsan; Carolina F.Sembiring; Wilson Rajagukguk (Universitas Kristen Indonesia, 2024)
The era of progress and development has made four-wheeled vehicles, or cars, a basic necessity for the middle to upper-class society. This is evident from the increasing purchase of used cars every year. The number of car users continues to rise, resulting in various complex issues. One of the main issues is the worsening traffic congestion, leading to an increase in road accidents. The automotive service industry continues to evolve, providing adequate facilities. When these services are delivered effectively, they are used to enhance customer satisfaction. A quantitative approach is employed, and it has a cause-and-effect relationship design for the specific variables. The research findings are as follows: service quality has a positive and significant impact on customer satisfaction, with low significance (0.000 < 0.05). Similarly, the company image has a positive and significant effect on customer satisfaction, with low significance (0.004 < 0.05). Furthermore, there is a positive and significant simultaneous impact of the variables on customer satisfaction, as evidenced by the high F-value (191.345 > 3.136) and low significance level (0.000 > 0.05). In conclusion, the null hypothesis (H0) is rejected, and the alternative hypothesis (Ha) is accepted, indicating that service quality and company image significantly influence customer satisfaction. Keywords: Service Quality, Corporate Image, and Customer Satisfaction